Acid bone lysates reduce bone regeneration in rat calvaria defects - Strauss, Franz‐Josef (J Biomed Mater Res A, 2020)
Acid bone lysates (ABLs) represent the growth factors and other molecules released during autologous graft resorption. However, the impact of these bone‐derived growth factors on the healing of bone defects has not yet been investigated. The aim of the present study was, therefore, to examine the impact of ABLs adsorbed to collagen membranes on bone regeneration. To this end, in 16 female Sprague Dawley rats, a standardized 5‐mm‐diameter critical size defect on the calvarial bone was created. The defects were covered with collagen membranes that had been soaked either in serum‐free media or ABLs followed by lyophilization. After a healing period of 4 weeks, micro‐computed tomography (μCT) and histological analyses by means of undecalcified thin ground sections were performed. μCT analysis of the inner 4 mm of the calvaria defect showed a greater bone defect coverage in the control group when compared to ABL group, 29.8% (confidence interval [CI]: 17.7–50.3) versus 5.6% (CI: 1.0–29.8, p = .03), respectively. Moreover, we found significantly more absolute bone volume (BV) in the control group when compared to ABL group, 0.59 mm(3) (CI: 0.27–1.25) versus 0.07 mm(3) (CI: 0.06–0.59, p = .04), respectively. Histomorphometry confirmed these findings with a relative BV in the central compartment of 14.1% (CI: 8.4–20.6) versus 5.6% (CI: 3.4–7.9, p = .004), respectively. These findings indicate that bone‐derived growth factors contained in ABLs are able to attenuate bone regeneration within collagen membranes.